Comparison between digital photogrammetric systems - Ruzgienė, Birutė (Geodesy and Cartography, 2012)
The usage of Digital Photogrammetric Systems leads to increasing the mapping capabilities and efficiency through a full automation or in some cases half automation of mapping procedures. The digital image processing has possibility to improve the photogrammetric mapping implementation concerning the functionality and performance results relation. The goal of research is to investigate the functionality, flexibility and efficiency of two Digital Photogrammetric Mapping Systems for 3D surface modelling from aerial photographs. The experimental photogrammetric measurements have been carried out using DDPS software (Photogrammetric Package for Digital Aerial Photographs) as well as DPW (Digital Photogrammetric Workstation) LISA FOTO. The results of comparison between these two photogrammetric software show capabilities and possibilities for getting best results in digital photogrammetric processing. The analysis demonstrates that DDPS does not fulfil fully a typical workflow in digital photogrammetric mapping. However, the digital surface modelling is more efficient in time‐consuming. There is no doubt that DPW LISA FOTO together with image processing module LISA BASIC have more priorities, potentials and leads to wide applications. Despite this fact, DPW work is more complicated than DDPS in such aspects as stereo model creation, interpretation capabilities etc. The best digital photogrammetric mapping work flow could be achieved when integrating these two systems for getting a more efficient and highest productivity.First published online: 03 Aug 2012